The Smithsonian guides to historic America : - Dunn, Jerry Camarillo (Stewart, Tabori & Chang, 1998)
Each volume in this series features up to da te site information that includes location, visiting hours, phone numbers, and fee information, plus additional travel t ips. Maps offers broader views of each area and help plan yo ur own trips of discovery.